Integrasi Pendidikan Karakter dalam Pembelajaran PAUD Untuk Mengembangkan Emosi Positif Anak - Ghinaa Salsabila Zulya; Asep Kurnia Jayadinata; Dhea Ardiyanti (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to examine strategies for integrating character education in Early Childhood Education (ECE) to enhance children’s positive emotional development. Character education is considered a fundamental foundation for fostering personality development, self-regulation, and social skills during early childhood. This study employed a qualitative descriptive approach involving six ECE teachers selected based on teaching experience and active engagement in classroom practices. Data were collected through observations and in-depth interviews conducted in Purwakarta Regency, West Java, Indonesia, in 2025. The findings indicate that character education was consistently embedded in daily learning activities through lesson planning using the B3 approach (Playing, Storytelling, and Singing), supported by teacher modeling. Core character values such as independence, empathy, discipline, and responsibility emerged as dominant outcomes, contributing to children’s emotional regulation, self-confidence, and social awareness. Teacher consistency and parent collaboration were identified as key supporting factors, while diverse child characteristics and limited parental involvement posed challenges. This study offers a theoretical contribution to the discourse on character education in ECE and supports the achievement of SDG 4 (Quality Education) and SDG 3 (Good Health and Well-being).